34.7k views
5 votes
"Verify the identity of (sinx cosx)^2/sinx cosx = 2 + secx cscx"

this is for a friend and she's needing help big time

2 Answers

2 votes

(sinx + cosx)^2/((sinx)(cosx)) = 2 + (secx)(cscx)
(sinx + cosx)^2/((sinx)(cosx)) = 2 + 1/(sinxcosx); subtract 1/sinxcosx both sides
(sinx + cosx)^2/((sinx)(cosx)) - 1/(sinxcosx)= 2; multiply through by sinxcosx
(sinx + cosx)^2 -1 = 2(sinxcosx)
sin^2 + 2sinxcosx + cos^2 - 1 = 2(sinxcosx); since sin^x + cos^2x = 1
1 + 2sinxcosx -1 = 2sinxcosx
2sinxcosx = 2sinxcosx
User Marcus Whybrow
by
5.9k points
7 votes

Step by step answer:

The identity should be:


\displaystyle ((\sin x+ \cos x)^2)/(\sin x \cos x) = 2 + \sec x\csc x

You missed a + there in the numerator, otherwise it would not be an identity.

Expand the square on the numerator:


\displaystyle (\sin^2x+ 2\sin x\cos x+\cos^2x)/(\sin x \cos x) = 2 + \sec x\csc x

Replace
\sin^2x with
1-cos^2x\:


\displaystyle (1-\cos^2x+ 2\sin x\cos x+\cos^2x)/(\sin x \cos x) = 2 + \sec x\csc x

Combine like terms:


\displaystyle (1+ 2\sin x\cos x)/(\sin x \cos x) = 2 + \sec x\csc x

Distribute the denominator through each term of numerator:


\displaystyle (1)/(\sin x \cos x )+ (2\sin x\cos x)/(\sin x \cos x ) = 2 + \sec x\csc x

Simplify the second fraction:


\displaystyle (\sin x)/( \cos x )+ 2 = 2 + \sec x\csc x

Use the reciprocal identities: sin(x)=1/csc(x) and cos(x) = 1/sec(x):


\sec x\csc x+ 2 = 2 + \sec x\csc x

Re-ordering:


2+\sec x\csc x = 2 + \sec x\csc x

User Prahack
by
6.1k points